PEMBERDAYAAN KELOMPOK USAHA BABY FISH CRISPY DESA MULYOAGUNG NGANTANG KAB. MALANG - Churiyah, Madziatul; Arief, Muh.; Sholikhan; Dharma, Buyung Adi (Transpublika Publisher, 2022)
The agricultural sector, especially fisheries, has played an important role in the social and economic development of the Indonesian state, because the indonesian population has a daily life as farmers, and the territory of Indonesia 2/3 is the water area. Mulyoagung Village in Ngantang District is one of the villages located in the area around the Selorejo reservoir. In addition to farming, the main income of the community is dependent on the existence of the Selorejo reservoir, which is catching fish. Fish catches are sold in their unprocessed state to middlemen at a very low price since they lack the knowledge to process fish into various processed foods. Only about a year ago there was an attempt not to sell the fish in its raw condition, but to be sold in a mature state, in the hope that the price would be higher and not be played with by middlemen. By adopting from crispy mushrooms, baby fish is processed in crispy form. Through various trainings and assistance, including training on making crispy various flavors of basic uceng and wader fish, frying techniques, oil slicer techniques, product packaging as well as labeling and marketing, There has been steady growth in both the quantity and quality of this business, and it is now even being exported off the island.